2017
DOI: 10.18203/2394-6040.ijcmph20172180
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity pattern among school going adolescent girls of a North Indian district

Abstract: Background: The objective of the study was to assess the morbidity pattern among school going adolescent girls in Lucknow district of North India.Methods: A cross-sectional study was carried out in urban and rural schools of Lucknow district. Multistage random sampling was used to select the requisite number of girls. A total of 847 adolescent girls between 10 and 19 years of age were interviewed and examined physically from head to toe and any signs and symptoms of illness were recorded. Statistical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Another study done at Belgaum, [7] the mean age of menarche was 13.6 years. However, in a study done among North Indian adolescent girls [8], the mean age was 12.8 years. While in a study conducted in Egypt [9], it was found that the mean age was 12.7 years.…”
Section: Methodsmentioning
confidence: 94%
“…Another study done at Belgaum, [7] the mean age of menarche was 13.6 years. However, in a study done among North Indian adolescent girls [8], the mean age was 12.8 years. While in a study conducted in Egypt [9], it was found that the mean age was 12.7 years.…”
Section: Methodsmentioning
confidence: 94%